The Impact of Educational Counseling on the Alteration of Athletic Identity among Adolescents (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. The article deals with the manifestation of athletic identity of senior students of secondary schools as a major precondition for the development of physical education among adolescents and health-favouring lifelong physical activity (Anderson, 2004; Bélanger, et al., 2011). The hypothesis of the paper is that under educational counseling, the evaluations of athletic identity among adolescents increase.Research aim was find out the impact of educational counseling (EC) on the alteration of athletic identity (AI) of adolescents.Research methods. In order to evaluate AI among adolescents, a methodology of EC was employed. To reveal issues faced by adolescents, questions of four types were employed: Exception, Miracle, Coping and Scale questions together with PA definition questions ( International Physical Activity Questionnaire short form). The evaluation of AI was performed with the Athletic Identity Questionnaire for Adolescents as developed by C. B. Anderson, L. C. Mâsse and A. C. Hergenroeder (2007) consisting of forty statements which were evaluated in the Likert scale from 1 to 5 by the research participants.The research involved 553 students (294 females and 259 males) whose age average was 16.75 ± 1.11 years. The students were randomly assigned to EC impact (253 students) and comparison (300 individuals) groups. The members of the impact group were counseled from one to six times regarding PA and other problems while the adolescents constituting the comparison group merely indicated their PA and other issues; they were not counseled.Research results. The evaluation of AI and its constituent parts in the impact and comparison groups were not statistically significant before EC (p  > 0.05).During the period of EC, the values of AI and its constituents regarding the importance of PA and incentives to be involved in PA statistically significantly improved in the adolescents facing problems connected with PA of the impact group.EC was more efficient for those adolescents who were not sufficiently involved in classes of physical education. They showed significant (p  < 0.05) improvement not only in terms of AI but also concerning the values of the importance of PA and the evaluations of social incentives (general incentives).Discussion and conclusions. EC positively impacted the alteration of AI among adolescents. During the period of EC, statistically significant (p < 0.05) improvement was observed in the evaluations of AI regarding its constituent parts, the importance of PA and incentives for PA among the adolescents who had been facing problems linked to PA. The AI values statistically significantly (p < 0.05) increased in both males and females during the period of EC. The impact of EC on the athletic identity was insignificant (p > 0.05) in adolescents exhibiting problems in communication with teachers of physical education.Keywords: educational counseling, athletic identity, physical activity.